Influence of diet on the morphology of the ruminal papillae in reindeer calves (Rangifer tarandus tarandus L.) - Josefsen, Terje D.; Aagnes, Tove H.; Mathiesen, Svein D. (Rangifer, 1996)
The influence of diet on the morphology of reindeer ruminal papillae was investigated in 4 groups of 3 free-ranging reindeer calves at different seasons, and in 11 groups of 3 reindeer calves fed experimental diets. Length, cross-sectional perimeter and density (number/cm2) of the ruminal papillae were measured in 4 sample sites in the rumen wall, and the ruminal surface enlargement factor (SEF) was calculated at each sample site. The range of group means were 2.3 to 3.4 mm for overall papillary length (mean of the four sample sites), 2.2 to 3.5 mm for overall cross-sectional perimeter, 85 to 189 papillae/cm2 for overall papillar density and 5.8 to 18.6 for overall SEF. Differences between sample sites wete observed, atrium ruminis having the highest and caudodorsal blind sac the lowest SEF (25% over and 24% below overall value, respectively). The differences between sample sites were considered to be small, indicating a homogenous ruminal content. The SEF of free-ranging animals showed a seasonal pattern, with high overall SEF (18.6) in September (late summer) and lower overall SEF 9.1) in April (late winter). Groups fed timothy silage with low content of cellulose (18.7% of dry matter) showed highest overall SEFs of the fed animals (17.8 and 13.9), while groups fed timothy silage with high content of cellulose (30.4%' of dry matter) showed lowest overall SEFs (5.8 and 7.0), indicating low ability to ferment silage with high content of cellulose. The SEF in animals fed experimental diets seemed partly to be influenced by SEF at the beginning of the feeding period.